2010
DOI: 10.1186/1471-2229-10-165
|View full text |Cite
|
Sign up to set email alerts
|

Development of Efficient Plant Regeneration and Transformation System for Impatiens Using Agrobacterium tumefaciens and Multiple Bud Cultures as Explants

Abstract: BackgroundImpatiens (Impatiens walleriana) is a top selling floriculture crop. The potential for genetic transformation of Impatiens to introduce novel flower colors or virus resistance has been limited by its general recalcitrance to tissue culture and transformation manipulations. We have established a regeneration and transformation system for Impatiens that provides new alternatives to genetic improvement of this crop.ResultsIn a first step towards the development of transgenic INSV-resistant Impatiens, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 40 publications
0
7
0
1
Order By: Relevance
“…However, it should be recalled that use of these compounds individually did not help in H. perforatum transformation in our previous attempts (Franklin et al, 2007 ). Nevertheless, application of a mixture of antioxidants could be useful, as it has been shown to improve the efficiency of Agrobacterium -mediated transformation in a number of other recalcitrant plant species (Dan, 2008 ; Dan et al, 2010 , 2015 ). It is also important to understand the signaling events that trigger H. perforatum defense activation upon Agrobacterium interaction.…”
Section: Future Perspectives and Strategies For H Perforatmentioning
confidence: 99%
“…However, it should be recalled that use of these compounds individually did not help in H. perforatum transformation in our previous attempts (Franklin et al, 2007 ). Nevertheless, application of a mixture of antioxidants could be useful, as it has been shown to improve the efficiency of Agrobacterium -mediated transformation in a number of other recalcitrant plant species (Dan, 2008 ; Dan et al, 2010 , 2015 ). It is also important to understand the signaling events that trigger H. perforatum defense activation upon Agrobacterium interaction.…”
Section: Future Perspectives and Strategies For H Perforatmentioning
confidence: 99%
“…Ntui et al (2010) reduced ethylene production by explants after Agrobacterium infection, even as the ACC gene expression reduced and increased the transformation rate. A cytological study by Dan et al (2010) on melon epidermal and sub-epidermal cells revealed a lower regeneration rate of the infected explants which can be related to the disability of cells in causing regeneration. Also, this may be due to the genetic instability of the infected meristematic parts.…”
Section: Discussionmentioning
confidence: 98%
“…), the petaloid sepals of Impatiens (Geuten et al, 2006) or the first whorl tepals from Tricyrtis (Liliales). These species have indeed been reported to be stably transformable (Adachi et al, 2005;Nakano et al, 2007;Feng et al, 2009;Dan et al, 2010).…”
Section: Does Evolvability Of B-gene Expression Contribute To Evolutimentioning
confidence: 95%